Rural Aging in 21st Century America
XVI, 384 p.
Keywords: This book investigates sociological, demographic and geographic aspects of aging in rural and nonmetropolitan areas of the United States. Population aging is one of the most important trends of the 20th and 21st centuries, and it is occurring worldwide, especially in more developed countries such as the United States. Population aging is more rapid in rural than urban areas of the U.S. In 2010, 15 percent of the nonmetropolitan compared to 12 percent of the metropolitan population were 65 years of age and older. By definition rural communities have smaller sized populations, and more limited healthcare, transportation and other aging-relevant services than do urban areas. It is thus especially important to study and understand aging in rural environments. Rural Aging in 21st Century America contributes evidence-based, policy-relevant information on rural aging in the U.S. A primary objective of the book is to improve understanding of what makes the experience of rural aging different from aging in urban areas and to increase understanding of the aged change the nature of rural places. The book addresses unique features of rural aging across economic, racial/ethnic, migration and other structures and patterns, all with a focus on debunking myths about rural aging and to emphasize opportunities and challenges that rural places and older people experience. .